2015
DOI: 10.1021/acs.langmuir.5b00896
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Role of the Double Bond Isomerism in the Steroid B-Ring on the Membrane Properties of Sterols. Grazing Incidence X-Ray Diffraction and Brewster Angle Microscopy Studies

Abstract: Three cholesterol precursors-desmosterol, zymosterol, and lanosterol-were comprehensively characterized in monolayers formed at the air/water interface. The studies were based on registration of the surface pressure (π)-area (A) isotherms complemented with in situ analysis performed with application of modern physicochemical techniques: grazing incidence X-ray diffraction (GIXD) and Brewster angle microscopy (BAM). In this approach we were interested in the correlation between molecular structures of the studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Likewise, locations of ve other C]C bonds could be obtained. Therefore, the above evidence indicated that the detailed structure for one of the PC 38:6 isomers should be PC 16:0_22:6 (4,7,10,13,16,19).…”
Section: Application Of This Vaca Reaction In Structural Lipidomicsmentioning
confidence: 89%
See 1 more Smart Citation
“…Likewise, locations of ve other C]C bonds could be obtained. Therefore, the above evidence indicated that the detailed structure for one of the PC 38:6 isomers should be PC 16:0_22:6 (4,7,10,13,16,19).…”
Section: Application Of This Vaca Reaction In Structural Lipidomicsmentioning
confidence: 89%
“…The C]C bonds in positional isomers of unsaturated lipids endow them with different structures and functions in living organisms. 2,[11][12][13] For instance, lipids with cis-C]C in the fatty acyl chain were found to modulate plasma membrane domain registration/anti-registration. 14 Signicant correlations between the C]C positional isomer and the onset/progression of breast cancer were also observed.…”
Section: Introductionmentioning
confidence: 99%
“…1). Cs -1 150 mN/m 19,30) . The elasticity values for each monolayer was calculated at surface pressure of 30 mN/m (Table 1) In bilayer studies 14) , Lan at 50 mol% in DOPC bilayer resulted in the dehydration.…”
Section: Interaction Of Dopc and Lan Based On Excess Area Analysismentioning
confidence: 99%
“…Particularly, the double bond of B ring in sterols induces non planar structure, which decreases membrane packing 19) . Hence, Lan is classified in non-membrane active sterols 8) because Lan did not produce any co-existing solid or liquid phases in phospholipid bilayers 20) .…”
Section: Introductionmentioning
confidence: 99%
“…Brewster angle microscopy (BAM) is a powerful technique that provides a quantitative structural analysis of Langmuir monolayers. BAM imaging along with Langmuir techniques or X-ray reflectometry have also been widely used to study domain morphology and lateral phase separation in lipid monolayers and interfaces [ 12 , 13 , 14 , 15 , 16 ]. However, apart from cholesterol, the investigations on the other membrane sterols are not comprehensive in nature based on BAM approaches.…”
Section: Introductionmentioning
confidence: 99%